2018
DOI: 10.1101/351627
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultralarge Modulation of Single Wall Carbon Nanotube Fluorescence Mediated by Neuromodulators Adsorbed on Arrays of Oligonucleotide Rings

Abstract: Non-covalent interactions between single-stranded DNA (ssDNA) oligonucleotides and single wall carbon nanotubes (SWNTs) have provided a unique class of tunable chemistries for a variety of applications. However, mechanistic insight into both the photophysical and intermolecular phenomena underlying their utility is lacking, resulting in obligate heuristic approaches for producing ssDNA-SWNT based technologies. In this work, we present an ultrasensitive "turn-on" nanosensor for neuromodulators dopamine and nore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…We therefore propose an alternative mechanism, whereby DOX modulates nucleobase stacking on the nanotube surface, inducing a conformational change in the DNA. The increased accessibility of solvent to the SWNT surface induces a red-shift in fluorescence emission, , while changes to the periodic surface potential on the nanotube surface modulate exciton lifetimes, which results in an increase in fluorescence emission . This increase in fluorescence is likely dependent on the formation of a highly ordered arrangement of the polymer on the SWNT surface, corroborated by the dependence on DNA surface coverage density we observe.…”
Section: Resultssupporting
confidence: 70%
“…We therefore propose an alternative mechanism, whereby DOX modulates nucleobase stacking on the nanotube surface, inducing a conformational change in the DNA. The increased accessibility of solvent to the SWNT surface induces a red-shift in fluorescence emission, , while changes to the periodic surface potential on the nanotube surface modulate exciton lifetimes, which results in an increase in fluorescence emission . This increase in fluorescence is likely dependent on the formation of a highly ordered arrangement of the polymer on the SWNT surface, corroborated by the dependence on DNA surface coverage density we observe.…”
Section: Resultssupporting
confidence: 70%
“…Prior work has confirmed that this stabilization effect represents a strong and selective binding interaction between the molecular analyte and the polymer-SWNT assembly. 38 To confirm we may attribute the additional stability provided to ProLoop-SWNT assemblies by selective binding of WGA, we showed that WGA by itself does not associate strongly to SWNT, and showed that attempted assembly of WGA with SWNT produced a highly unstable complex (SI. 15).…”
Section: Probing the Interaction Between Peptoid-swnts And Wgamentioning
confidence: 85%
“…This technology makes use of an SWNT noncovalently functionalized with single-strand (GT) 6 oligonucleotides to form the nIR catecholamine nanosensor (nIRCat). nIRCats respond to DA with Δ F / F of up to 24-fold in the fluorescence emission window of 1000 to 1300 nm ( 24 ), a wavelength range that has shown utility for noninvasive through-skull imaging in mice ( 25 ).…”
Section: Introductionmentioning
confidence: 99%